Cholangiocarcinoma: Risk Factors, Diagnostic Tools, and Current Treatment Options - Adli Putra Nugraha; Baiq Ghassani Kayla; Febbi Anggy; Ni Made Utami Wulandari; Wina Arsylia Fakar; Philip Habib (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Cholangiocarcinoma is a disease caused by the differentiation of cells in the bile epithelium or liver parenchyma into malignant cells called cholangiocytes. This literature review presents the current risk factors, diagnostic tools, and treatment choices of cholangiocarcinoma. Publication about the current risk factors, diagnostic tools, and treatment choices of cholangiocarcinoma were collected from the Pubmed database until August 25, 2022. The keywords of the research were “cholangiocarcinoma”, “risk factor”, “diagnostic”, and “treatment”. Cholangiocarcinoma has many risk factors, from choledochal cysts, and primary sclerosing cholangitis, to asbestos exposure. The diagnosis of cholangiocarcinoma is difficult and requires the combined interpretation of different diagnostic modalities. Examinations that can be done for the diagnosis and staging of cholangiocarcinoma are MRI and CT. However, if the diagnosis remains uncertain, endoscopic examination and tissue sampling may be performed. After the diagnosis, there are several treatments, namely surgical therapy (surgical excision of bile duct tumors), endoscopic therapy (endoscopic biliary dilatation), radiological therapy (percutaneous transhepatic palliative biliary dilatation), chemotherapy and radiotherapy, and photodynamic therapy. Cholangiocarcinoma is a malignancy of cells in the biliary epithelium or liver parenchyma (cholangiocytes) that has many risk factors. The diagnosis of cholangiocarcinoma is difficult and requires a combined interpretation of the different diagnostic modalities, including MRI, CT, endoscopy, and tissue sampling. After the diagnosis, there are several treatments, namely surgical therapy, endoscopy, radiology therapy, chemotherapy and radiotherapy, and photodynamic therapy.